The Use Of Digital Storytelling To Enhance The Students Speaking Ability (RETAIN, 2022)
This study aimed to identify whether digital storytelling can enhance students' speaking ability in learning English. The research was conducted using a descriptive quantitative method of the pre-test and post-test control group design for 8th-grade junior high school students at one of the private Junior High Schools in Surabaya, Indonesia. A total of 40 students divided equally into the control and experimental groups participated in this study. Students included in the experimental group were given treatment by learning English using digital storytelling, while students in the control group are not given this treatment. The instrument used to collect the data are speaking test and analyzed with descriptive analysis. The results of statistical analysis of the pre-test and post-test scores conducted on the two groups of students indicate a significant difference in the post-test results of the two groups. The average score of the group of students who were not given treatment only increased by 17.02%, while the group of students who received treatment increased by 26.79%. The independent samples t test results using the Mann-Whitney method at a significance level of 95% (α = 0.05) also showed that the t value was 109.500 < t table 127.000 and the p-value was 0.009 < 0.05. This means that there is a significant difference in post-test results between the group that was given the treatment of digital storytelling and the group that was not given the treatment, thereby the researcher can conclude that digital storytelling can enhance students' speaking ability in learning English. Keywords: speaking ability, English language, digital storytelling, students.